Welcome to Dadsville : dad jokes for big kids - Graham, Pete (London, United Kingdom ; Chatswood, NSW ; Auckland, New Zealand : New Holland Publihers, 2017)
Dad jokes are in and of themselves an art form. The first step is that they have to be so bad they’re funny. They also have the sort of punchline that you should have saw coming but somehow didn’t. And they’re all a little embarrassing to laugh at. But hey, if everyone else is probably groaning, laughing or perhaps doing both at the same time, your goal has been achieved! Radio DJ Pete Graham is the ‘King’ of the dad joke. Every day he posts a dad joke on his Facebook page and brings a laugh to thousands of people. You could say that Pete resides is a permanent state of ‘Dadsville’. Here, for the first time, is a collection of Pete Graham’s favourite dad jokes in Welcome to Dadsville!
Keywords: Fathers -- Humor; Fatherhood -- Humor; Father and child -- Humor; Wit and humor; Australian; Humor